INFLUENCE OF THE SEALING ON APPEARANCE AND TRANSMISSION OF TEMPERATURE DEFORMATIONS IN ELECTRONIC MODULES - KOVTUN, Igor; PETRASHCHUK, Svitlana; BOIKO, Juliy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The scientific result presented in this paper consists in development of the Lame-Gadolin theory about   interaction of joint thick-walled cylinders application to estimate strength of electronic components represented by  bodies of revolution and surrounding layer of compound sealed by an arbitrary shape subjected to thermal impacts in the temperature range from +70 to -60 deg C. The difference in the coefficients of linear thermal expansion and other physical and mechanical characteristics of compound and electronic components under the temperature changes produces a contact pressure on their contact area causing thermal strain and stress in materials of both bodies in the sealed structure. Within the framework of the axisymmetric problem, the stress-strain condition of the electronic component-compound system has been assessed in condition of thermal impact, due to which the pattern of the maximum total radial, circumferential and axial stresses has been revealed depending on their radial distribution and the temperature load mode. The stress estimation in the S2-29V resistor sealed with the EZK-25 compound inside the sealed electronic package has been performed at the constant temperature drop. The experimental method is proposed for determining the ultimate stresses in electronic components sealed with compound under stress and strain condition identical to the operational one. Experimental measurement of circumferential and axial strains was carried out by using method of electrotensometry. Thermal impacts were reproduced in the thermostat and the climatic chamber. Technological methods for protection of electronic components in the structures of electronic packages sealed with compound has been proposed by embedding elastic and dissipative joints between electronic components and a sealant, and the effectiveness of their application is experimentally evaluated based on determination of the damping coefficient.
Keywords: sealed electronic package; electronic component; compound; strength; stress and strain condition